2021
DOI: 10.22146/jpki.63251
|View full text |Cite
|
Sign up to set email alerts
|

Factors Correlated With Medical Students Anxiety in Clinical Skills Examination

Abstract: Background: Test anxiety is one of the medical student’s problems that need attention in medical education. Test anxiety can have negative effect on students such as negative self-evaluation beliefs, low motivation, poor performance, and decreased concentration which can result in increased dropout rates and trigger general anxiety. Test anxiety can affect performance on clinical skill examination and outcomes.Aim: To identify factors correlated with medical students’ anxiety in clinical skills examination.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…(10) Khalid I. Khoshhal et al found a prevalence of exam anxiety in Saudi Arabia of 65%, which is also lower than our ndings. (12) In Pakistan Brand and Schoonheim -Klein et al reported greater stress levels among dental students during OSCE in comparison to written and practical assessment methods,they said students had to prepare better for OSCEs and thier expectation to pass OSCE was also signi cantly higher which might be the cause of stress(18)in another study students said that there is a need to reassess the amout of the study materials allocated in their study and this could be the cause of thier anxiety. ( 12)…”
Section: Variablesmentioning
confidence: 99%
“…(10) Khalid I. Khoshhal et al found a prevalence of exam anxiety in Saudi Arabia of 65%, which is also lower than our ndings. (12) In Pakistan Brand and Schoonheim -Klein et al reported greater stress levels among dental students during OSCE in comparison to written and practical assessment methods,they said students had to prepare better for OSCEs and thier expectation to pass OSCE was also signi cantly higher which might be the cause of stress(18)in another study students said that there is a need to reassess the amout of the study materials allocated in their study and this could be the cause of thier anxiety. ( 12)…”
Section: Variablesmentioning
confidence: 99%